Antibacterial activity of different fractional extracts of cerastium glomeratum - Himayat Ullah; Muhammad Hubaib; Muhammad Israr; Muhammad Mushtaq; Muhammad Zeeshan; Muhammad Mustafa (Journal of Tropical Pharmacy and Chemistry, 2020)
Every plant available in the universe is not produced to be the part of biodiversity, but is also produced to obtain medicinal purposes. The medicinal value of the plant is due to the availability of various chemical compounds [1]. Since prehistoric time, the crude extract of plant is used to cure various diseases, although the biologically active components of the plant were unidentified [2]. In the present study the antibacterial activity is performed for various extracts of cerastium glomeratum. The plant cerastium glomeratum was collected from near kalpani river Mardan, Pakistan and was identified by lecturer Israr department of botany GPGC Mardan, Pakistan. The plant was dried under shade and grinded into powder form. The extraction process was done by using soxhlet apparatus, reflux condenser and maceration process using ethanol as a solvent. The extract was divided into different fractions of n-hexane, DCM, ethyl acetate and water. These four extracts were tested against gram positive (staphylococcus aureus) and gram negative (E.coli) bacteria using well diffusion technique. The water extract show a wide range inhibition zone against both gram positive and gram negative bacteria while n-hexane, DCM and ethyl acetate fractions show no zone of inhibition against bacteria. In effort to find new antibacterial compounds cerastium glomeratum seems to be a good plant for additional phytochemical studies.